Illocutionary Acts on Harry Potter And The Deathly Hallows Movie - Camelia, Mega; Suastini, Ni Wayan; Ayomi, Putu Nur (Institut Pariwisata dan Bisnis Internasional, 2023)
This study is focused to analysis the types of illocutionary acts produced by Harry Potter and Hermione Granger in Harry Potter and The Deathly Hallows Part 2 movie. This study used theory proposed by Searle (1979) to classify the types of illocutionary acts. The qualitative method is used in this study and used observation method in collecting the data. This study used formal and informal method in presenting the data. According to the data analysis there are 48 utterances of illocutionary act. The highest of illocutionary act produced by Harry and Hermione is directive with percentage 48%. In the second is assertive with percentage 25%. The third is expressive with percentage 15% and the last is commissive with percentage 13%.